formulasi dan uji mutu fisik sediaan lip balm dari ekstrak daun nanas (Ananas comosus L) - Cikra Safitri; fiorentina astrid (Fakultas Sains, Teknologi, dan Analsisi Institut ilmu Kesehatan Bhakti Wiyata, 2026)
The vulnerability of lips to environmental factors has created a need for safe and effective care products. With more and more people becoming aware of the potential risks of synthetic chemicals, the demand for natural cosmetics is increasing. This study aims to utilize pineapple leaf waste (Ananas comosus L.), which is rich in beneficial compounds, to make lip balm cosmetics, as well as to check the physical quality of the product. This study was conducted experimentally, beginning with the extraction of pineapple leaves by maceration using 70% ethanol. The resulting extract was then made into three types of lip balm consisting of a base formula without extract (F1), extract with a concentration of 0.3% (F2), and extract with a concentration of 0.6% (F3). All products were tested for physical quality, including organoleptic testing, stability, spreadability, and pH measurement, in accordance with existing standards (SNI). The results of the physical quality test showed that formulas F1 and F2 met all requirements. Specifically, all formulas had spreadability in accordance with SNI (between 3–7 cm) and a pH level that was safe for the lips (4.5–6.5). The pH of products containing extract (F2 and F3) was 5, slightly lower than the base formula (F1=6) due to the addition of extract, which tends to have acidic properties. However, in the formula with the highest extract concentration (F3, 0.6%), the resulting product is less homogeneous. Keywords: lip balm; pineapple leaf extract; formulation; physical quality